Bifunctional properties and characterization of a novel sialidase with esterase activity from Bifidobacterium bifidum. Issue 11 (2nd November 2018) - Ashida, Hisashi; Tanigawa, Kana; Kiyohara, Masashi; Katoh, Toshihiko; Katayama, Takane; Yamamoto, Kenji
ABSTRACT: Sialidases catalyze the removal of terminal sialic acid from various complex carbohydrates. In the gastrointestinal tract, sialic acid is commonly found in the sugar chain of mucin, and many enteric commensals use mucin as a nutrient source. We previously identified two different sialidase genes in Bifidobacterium bifidum, and one was cloned and expressed as an extracellular protein designated as exo-α-sialidase SiaBb2. The other exo-α-sialidase gene ( siabb1) from the same bifidobacterium encodes an extracellular protein (SiaBb1) consisting of 1795 amino acids with a molecular mass of 189 kDa. SiaBb1 possesses a catalytic domain that classifies this enzyme as a glycoside hydrolase family 33 member. SiaBb1 preferentially hydrolyzes α2, 3-linked sialic acid over α2, 6-linked sialic acid from sialoglycan, which is the same as SiaBb2. However, SiaBb1 has an SGNH hydrolase domain with sialate- O -acetylesterase activity and an N-terminal signal sequence and C-terminal transmembrane region. SiaBb1 is the first bifunctional sialidase identified with esterase activity. Abbreviations : GalNAc: N-acetyl-D-galactosamine; Fuc: L-fucose; Gal: D-galactose Graphical abstract: : Sialidase (SiaBb1) of Bifidobacterium bifidum had both activities of sialate- O - acetylesterase activity with SGNH hydrolase domain and hydrolysis activity with catalytic domain